Arts Based Education Relevance in Seratwedhatama by K.G.P.A.A Mangkunegaran IV in Nusantara - Pambudi, Setyo; Utomo, Sigit Tri; Muanayah, Nur Alfi (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2020)
This research is intended to find out the values of Islamic Education in the Wedhatama book written by KGPAA Mangkunegaran IV which is very relevant today. This research is a type of literature study research by looking for theoretical references that are relevant to the cases or problems found. Data collection techniques using documentation, observation and study literature Tajusalatin Fiber. The data that has been obtained are then analyzed using descriptive analysis methods. Descriptive analysis method is carried out by describing the facts which are then followed by analysis, not only describing, but also providing adequate understanding and explanation. To understand the full meaning of Wedhatama, it is necessary to begin with knowing the outline of the contents of the Pupuh tembang pangkur, which is an opening of the teachings that in general to walk towards